Implementasi Model Problem Based Learning (PBL) dalam Meningkatkan Keterampilan Pemecahan Masalah Matematis Peserta Didik Kelas VIII B di SMP Negeri 15 Palu - Pratiwi, A. Rezky; Sukayasa; Lantang, Nortje D. J (Papanda, 2025)
This study aims to improve students' Mathematical Problem Solving Skills (KPMM) through the application of the Problem Based Learning (PBL) learning model. This study is a collaborative Classroom Action Research (CAR) between researchers and mathematics teachers, which was carried out in two cycles. The subjects of the study were grade VIII B students of SMP Negeri 15 Palu in the even semester of the 2024/2025 academic year. The instruments in this study consisted of learning tools such as syllabus, Lesson Implementation Plan (RPP), teaching materials, and Student Worksheets (LKPD), as well as data collection instruments in the form of observation sheets and KPMM tests. Data analysis techniques used include narrative descriptive analysis for qualitative data and descriptive statistical analysis for quantitative data. The results of the study indicate that the application of the PBL model can improve students' KPMM. The average KPMM score increased from 79.79 in cycle I to 90.31 in cycle II. Improvements occurred in all aspects of KPMM measured. Thus, it can be concluded that the application of Problem Based Learning is effective in improving the mathematical problem-solving abilities of class VIII B students at SMP Negeri 15 Palu